Principles and Practices of Seismic Isolated Buildings - Abrishambaf, Amin (Eastern Mediterranean University (EMU), 2009)
ABSTRACT: Earthquake design philosophy based on capacity, directs the following two unpleasant states: 1. The situation that continues to increase the elastic strength and stiffness; in fact this is not economical and also cause higher floor accelerations. 2. The situation that limits the elastic strength and increasing ductility by detailing; indeed this approach is the acceptance of non-repairable structural damages. Base isolation is a different approach than the mentioned ones. It is based on the concept, which reducing the seismic demands rather than increasing the earthquake resistance capacity of the structure. On the other hand, application of base isolators to the structure reduce elastic base shear by shifting period of the structure and provide better performing structure that will remain essentially elastic during large earthquakes. However, in this thesis, general information about seismic isolated structures such as type of isolators, world-wide applications, practical applications, properties, code requirements and different processes required for designing various seismic isolators are discussed. Then, 3 different buildings (3, 6 and 9 story) which were isolated by 3 various isolators (Lead Rubber Bearing, High Damping Rubber Bearing and Friction Pendulum System) were analyzed by applying dynamic response spectrum analysis, as a linear elastic analysis method, to evaluate the optimum one according to the seismic demands. Transmitted acceleration, maximum structural displacement and seismic coefficient for each building were shown in the different graphs. Furthermore, the 3 story optimum isolated building was compared with its conventional fixed base one in performance and material. Based on obtained results, it could be inferred that Lead Rubber Bearings represent minimum transmitted acceleration and seismic coefficient among other types. Low effective stiffness and high damping which is represented by Lead Rubber Bearings are the most important factors for this minimization. Structural displacement is minimized by Friction Pendulum Systems due to the high friction of coefficient which they produce. In addition, in rubber bearings transmitted acceleration and structural displacement is affected by damping of isolation system. Furthermore, in the comparison process of base isolated building with its conventional fixed base one , it is concluded that application of the base isolators to the structure increase cost of the building around 5.8 % of total cost. Keywords: Base isolation, Isolator, Cost, Earthquake, Strengthening. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Sismik Taban Yalitimli Binalarda Temel Prensip ve Uygulamalar. Kapasiteye dayanan deprem tasarim felsefesi bizi asagidaki iki kötü seçime yönlendirmektedir: 1. Elastik dayanimi sürekli olarak artirmak; Bu yaklasim ekonomik degildir ve yüksek kat ivmelerine sebep olmaktadir. 2. Elastik dayanimi sinirlandirmak ve detaylandirarak düktiliteyi artirmak; Bu yaklasim ise ileride binada tamir edilemeyecek yapisal hasarlarin kabülü sayilir.Sismik taban izolasyonu yukarida belirtilenlerden farkli bir yaklasimdir. Yapinin deprem direnç kapasitesini artirmak yerine sismik talepleri azaltmaya yönelik bir yaklasimi temel alir. Diger taraftan, yapiya taban yalitiminin uygulanmasi yapinin periyodunu kaydirarak elastik taban kesme kuvvetini azaltir. Bununla beraber büyük depremlerde esasen elastik davranisi koruyan daha iyi bir yapi performansi saglanmis olur. Bu tez çalismada izolasyon sistemleri, dünyadaki uygulamalari, pratik applikasyonu, özellikleri, yönetmelik esaslari ve degisik izolatörlerin tasarimi gibi konularda detayli bilgi verilmistir. Daha sonra ise degisik kat yüksekliklerine sahip (3, 6 ve 9), 3 ayri binaya 3 farki tip taban izolatörü (kursun çekirdek mesnet sistemi, yüksek sönümlü dogal kauçuk mesnet sistemi ve sürtünmeli sarkaç sistemi) uygulanarak response spektrum analizi yapilmistir. Farkli grafiklerde maksimum kat ivmeleri, maksimum deplasman ve taban kesme katsayilari karsilastirilmistir. Son olarak 3 katli ankastre ve izolatörlü yapilar performans ve malzemeye dayali olarak karsilastirilmistir. Elde edilen sonuçlardan yola çikarak kursun çekirdek mesnet sistemi digerleri arasinda minimum ivme ve sismik katsayiyi vermistir. Yüksek viskoz sönüm ve düsük rijitlik özellikleri bunu saglayan en önemli faktörlerdir. Yapisal deplasman sürtünmeli sarkaç sisteminde yüksek sürtünme katsayisina bagli olarak minimize edilmistir. Buna ilaveten, kauçuk mesnet sistemlerinde ivme ve yapisal deplasmanin izolasyon sisteminin viskoz sönümden etkilendigi söylenebilir. Sonuç olarak ankastre ve izolatörlü yapilar arasinda yapilan karsilastirmaya dayali olarak temel izolatörlü yapilarin toplam maliyeti 5.8% artirdigi gözlenmistir. Anahtar Kelimeler: Taban izolasyonu, Izolator, Maliyet, Deprem, Güçlendirme.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2009. Supervisor: Assist. Prof. Dr. Giray Özay.
Keywords: Civil Engineering; Earthquake Engineering; Earthquake Resistant Design; Concrete Earthquake Resistant Structures - Design; Base Isolation - Isolator - Cost - Earthquake - Strengthening